O conceito de racionalidade tecnológica no pensamento de Herbert Marcuse: origem, desenvolvimento e implicações sociais - Lima, Renê Ivo da Silva (2020)
The objective of this research is to understand the meaning of the concept of rationality technological development in Herbert Marcuse’s critical theory, its origin, development and its social implications. To apprehend the object of study of this work, the rationality research, the research uses as its main bibliographic reference the essay entitled Some social implications of modern technology, published in 1941, and the book One-Dimensional Man, published in 1964. The work has as methodology the theoretical research, in the which uses the exegetical understanding, development and exposition of the concept of technological rationality and Marcuse’s main ideas related to this concept. In this way, the research raises and proposes to answer the following question: what is the technological rationality? What is its origin, how does it develop and what are the its social implications? The result of this work is that the origin of rationality technology can be identified in the thinking of the main founders of science modern development, its development occurs through the technological production apparatus and its social implications are the reduction and paralysis of the negative-critical reason and the development of a technological society that integrates to its logic the overwhelming majority of alternatives of political transcendence. The work concludes that technological rationality is a instrument of domination, control and power committed to the maintenance and perpetuation of the established life project.